2008
DOI: 10.1007/s10437-008-9026-0
|View full text |Cite
|
Sign up to set email alerts
|

New Data on the Late Pleistocene of the Shakshuk Area, Jebel Gharbi , Libya

Abstract: The Jebel Gharbi represents the northern border of the Tripolitanian plateau. One of its most important features is the north facing slope which opens onto the Jefara coast. Since the 1990s the Italian and Libyan Joint Mission, directed by Barbara Barich of the University of Rome "La Sapienza," has been carrying out a project to define the cultural sequence of the region. At the beginning of the field campaign in 2000 an important settlement area was detected at the very base of the Jebel, near the village of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Sites are often found located close to water sources and streams. This pattern does not change in the LSA period (Barich et al 2006;Barich and Garcea, 2008;Mutri and Lucarini, 2008).…”
Section: Raw Materials Availabilitymentioning
confidence: 88%
“…Sites are often found located close to water sources and streams. This pattern does not change in the LSA period (Barich et al 2006;Barich and Garcea, 2008;Mutri and Lucarini, 2008).…”
Section: Raw Materials Availabilitymentioning
confidence: 88%
“…Perennial water sources presumably allowed human occupation MIS4 to MIS2 also outside the Nile valley, like e.g. at Kharga, in the Western Desert of Egypt (Kleindienst et al 2020;McDonald et al 2016), or at Shakshuck, in the Jebel Garbhi in northern Libya (Mutri and Lucarini 2008), for which support is also provided by evidence for episodic brief humid phases recognized also during glacial cycles, suggesting a sharp rise in probability in glacial MIS 2 especially in Northern and Eastern Sahara (Drake et al 2013).…”
Section: )mentioning
confidence: 99%
“…The valley of Shakshūk is located between the plains and the alluvial zone Jefara, near perennial streams which still provide water resources to the local vegetation. Because of the geological configuration of the terrain, it is suggested that these streams are associated with underground water sources, which are located 200 km south of Adrar Nafusah (Mutri & Lucarini, 2008). These streams played a large role in the settlement of this region, even during the driest periods of the Pleistocene and Holocene.…”
Section: The Lower Part Of Jadu Fieldmentioning
confidence: 99%
“…At the most important site in this area, SJ-00-56 (32˚01'N / 11˚57'E), 20,733 stone artefacts were found, and according to radioactive isotope C14 dating, belong to Upper Stone Age. Artefacts were different in size, shape and function, indicating the development of production due to the needs of the population (cutting meat, leather, and early species of plants) that inhabited this area, along with rich flora and fauna (Barich et al, 1995;Mutri & Lucarini, 2008;.…”
Section: The Lower Part Of Jadu Fieldmentioning
confidence: 99%